2010
DOI: 10.1111/j.1475-2743.2010.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in soil phosphorus status related to P budgets under maize monoculture and mineral P fertilization

Abstract: Monitoring soil phosphorus (P) changes under continuous cropping over decades is an important agronomic and environmental issue. The aim was to determine soil P dynamics in the plough layer as a function of cumulative P budgets (Bcum) across extended cropping periods (7, 12, and 17 yr) for four rates of mineral P fertilization. This field experiment was established in 1975 on a slightly alkaline, sandy loamy soil (luvic Arenosol). Soil P was assessed by three P tests: the concentration of P ions in solution (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 33 publications
4
44
4
1
Order By: Relevance
“…The stratification of phosphorus in NT maintains higher P concentration in the topsoil. Lupwayi et al (2006) found more bicarbonateextractable P in the top eight cm of soil with NT than with conventional tillage and 3.5 times greater available P concentration in the 0-5 cm soil layer than in the 5-15 cm layer in NT, similar to other studies (Franzluebbers and Hons 1996;Schwab et al 2006;Costa et al 2010;Messiga et al 2010;Calegari et al 2013). Corn roots could respond to this P heterogeneity in both root biomass (Barber 1971;Zhang et al 2012;Xia et al 2013;Deng et al 2014) and root morphology (Mollier and Pellerin 1999;Zobel et al 2007;Zhang et al 2012) variations. No-till tends to maintain higher soil moisture because of reduced soil evaporation (Scopel et al 2013).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The stratification of phosphorus in NT maintains higher P concentration in the topsoil. Lupwayi et al (2006) found more bicarbonateextractable P in the top eight cm of soil with NT than with conventional tillage and 3.5 times greater available P concentration in the 0-5 cm soil layer than in the 5-15 cm layer in NT, similar to other studies (Franzluebbers and Hons 1996;Schwab et al 2006;Costa et al 2010;Messiga et al 2010;Calegari et al 2013). Corn roots could respond to this P heterogeneity in both root biomass (Barber 1971;Zhang et al 2012;Xia et al 2013;Deng et al 2014) and root morphology (Mollier and Pellerin 1999;Zobel et al 2007;Zhang et al 2012) variations. No-till tends to maintain higher soil moisture because of reduced soil evaporation (Scopel et al 2013).…”
Section: Introductionsupporting
confidence: 74%
“…The experimental set-up was a split-plot plan replicated four times with two tillage practices (MP and NT) randomized into main plots and nine combinations of nitrogen (N) and P levels randomized into subplots including three N (0, 80, 160 kg N ha −1 every year) and three P (0, 17.5, and 35 kg P ha −1 ) applied, referred to as 0P, 0.5P and 1P. The 0P, 0.5P, and 1P corresponded to approximately 0, 0.5 and 1 time(s) the P annually exported at harvest (Messiga et al 2010). For the purpose of this study, we only considered the optimal level of 160 kg N ha −1 fertilization, the two tillage practices (MP and NT) and the three rates of P applications.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Zhu et al (2010) also reported that, in an 8-year field experiment, chemical fertilizers plus straw incorporation did not significantly increase soil TP and Olsen-P contents in subtropical region of China compared with chemical fertilizer application. Phosphorus accumulation in soil under a certain fertilization treatment or P budget usually exhibited a linear correlation with management history (Whalen and Chang 2001;Messiga et al 2010;Ciampitti et al 2011). In our study, the effect of management history on P accumulation in paddy soil was not fully elucidated due to the insufficient samples for each field monitoring period (Table 1), as this was not the main purpose of our study.…”
Section: Effects Of Organic Amendments On Soil P Accumulationmentioning
confidence: 70%
“…Linking P budget and soil P availability would require mechanistic models that are valid under a large range of soil conditions. Such models exist (Stroia et al 2007;Messiga et al 2010), but they are soil-dependent and thus require complex parameterisation based on isotopic dilution methods. Moreover, these models can only account for mineral fertiliser as input, not organic materials such as manure, compost, etc.…”
Section: Discussionmentioning
confidence: 99%